Identification of Novel Families and Classification of the C2 domain Superfamily Elucidate the Origin and Evolution of Membrane Targeting Activities in Eukaryotes - Zhang, Dapeng (2010)
Eukaryotes contain an elaborate membrane system, which bounds the cell itself, nuclei, organelles and transient intracellular structures, such as vesicles. The emergence of this system was marked by an expansion of number of structurally distinct classes of lipid-binding domains that could throw light on the early evolution of eukaryotic membranes. The C2 domain is a useful model to understand these events because it is one of the most prevalent eukaryotic lipid-binding domains deployed in diverse functional contexts. Most studies have concentrated on C2 domains prototyped by those in protein kinase C (PKC-C2) isoforms that bind lipid in a calcium-dependent manner. While two other distinct families of C2 domains, namely those in PI3K-C2 and PTEN-C2 are also recognized, a complete picture of evolutionary relationships within the C2 domain superfamily is lacking. We systematically studied this superfamily using sequence-profile searches, phylogenetic and phyletic-pattern analysis and structure-prediction. Consequently, we identified several distinct families of C2 domains including those respectively typified by C2 domains in the Aida (axin interactor, dorsalization associated) proteins, B9 proteins (e.g. Mks1 (Xbx-7), Stumpy (Tza-1) and Tza-2) involved in centrosome migration and ciliogenesis, Dock180/Zizimin proteins which are Rac/CDC42 GDP exchange factors, the EEIG1/Sym-3, EHBP1 and plant RPG/PMI1 proteins involved in endocytotic recycling and organellar positioning and an apicomplexan family. We present evidence that the last eukaryotic common ancestor (LECA) contained at least 10 C2 domains belonging to 6 well-defined families. Further, we suggest that this pre-LECA diversification was linked to emergence of several quintessentially eukaryotic structures, such as membrane repair and vesicular trafficking system, anchoring of the actin and tubulin cytoskeleton to the plasma and vesicular membranes, localization of small GTPases to membranes and lipid-based signal transduction. Subsequent lineage-specific expansions of Zizimin-type C2 domains and functionally linked CDC42/Rac GTPases occurred independently in eukaryotes that evolved active amoeboid motility. While two lipid-binding regions are likely to be shared by majority of C2 domains, the actual constellation of lipid-binding residues (predominantly basic) are distinct in each family potentially reflective of the functional and biochemical diversity of these domains. Importantly, we show that the calcium-dependent membrane interaction is a derived feature limited to the PKC-C2 domains. Our identification of novel C2 domains offers new insights into interaction between both the microtubular and microfilament cytoskeleton and cellular membranes.